Lung Disease in Antiphospholipid Syndrome - Maioli, Gabriella; Calabrese, Giulia; Capsoni, Franco; Gerosa, Maria; Meroni, Pier Luigi; Chighizola, Cecilia Beatrice (Seminars in respiratory and critical care medicine, 2019)
Antiphospholipid syndrome (APS) is an acquired prothrombotic condition characterized by vascular thrombosis and/or obstetric complications, in the persistent positivity of circulating antiphospholipid antibodies (aPLs). The clinical spectrum of manifestations associated with aPL positivity is progressively expanding, including the description of several lung manifestations. The most common pulmonary involvement related to aPL positivity is pulmonary embolism (PE), which has been reported to occur in 14.1% of APS patients during disease course. PE acknowledges a purely thrombotic etiology and thus might be accounted as a criterion for APS, making imperative to test aPL in young subjects with unprovoked PE. Pulmonary hypertension (PH) can manifest in APS patients, being the second most common lung complication of the syndrome, with a prevalence ranging between 1.8 and 3.5%. aPL-positive patients might present PH following a PE, might develop pulmonary arterial hypertension associated with connective tissue disease, or might present pulmonary venous hypertension due to Libman-Sacks endocarditis. Additional lung manifestations, such as diffuse alveolar hemorrhage, acute respiratory distress syndrome, and pulmonary fibrosis, are rarely described in APS patients; it is still not clear whether in these settings aPLs exert a pathogenic role or is a mere epiphenomenon. Hereby we discuss impact, clinical presentation, histopathologic findings, etiology, and treatment of each aPL-associated lung manifestation.